Value creation & capture around transport infrastructure station nodes in South Africa - Lombard, Samuel Hendrik (Department of Civil Engineering, 2017)
In the South African context, the infrastructure backlog is ever increasing and with limited government funding, the reality is that the gap will most likely never be closed. There are however, numerous value capturing mechanisms applied elsewhere in the world that can help with infrastructure funding, but little or none have been applied in a South African context yet. This report reviews the literature on value capturing, and explores whether or not it can be applied in transport infrastructure additions in South Africa. This report seeks to understand the applicability of the different mechanisms to a case study of the Gautrain project in Gauteng. Secondary data is used to evaluate the effect of the newly constructed stations on adjacent residential property values. This is done by looking at three variables, namely distance to station, analysis year and housing type. The data used in the analysis is validated by means of an ANOVA analysis, which is assessed by the F-test and a consequent Tukey's HSD test. This paper illustrates that value capturing is possible in a South African context. Stations such as Pretoria and Johannesburg indicated a direct correlation between increased property values and infrastructure additions and can therefore act as justification for value creation and consequent value capture. Further studies evaluating other variables should however still be conducted.